Serum cystatin C as a biomarker in non-Hodgkin lymphoma and its relationship with paraoxonase 1 activity - Mirjanić-Аzaric, Bosa; Mijic, Smiljana; Radic Savic, Zana; Stankovic, Sinisa; Malcic-Zanic, Dragana; Mihailovic Egeljic, Natasa; Stojisavljevic, Đorđe; ivetic, Bojana; Bogavac-Stanojevic, Natasa (Journal of Medical Biochemistry, 2026)
Background: The aim of this pilot study was to assess the potential of cystatin C (Cys C) as a biomarker in NHL and to explore its association with paraoxonase 1 (PON1) activity.  Methods: The study included 44 patients with B-cell NHL and 44 healthy subjects. Cys C was measured using the Cobas e 801 analyzer (Roche Diagnostics GmbH, Mannheim, Germany), while PON1and TAS were measured on the ILab 300+ system (Instrumentation Laboratory, Milan, Italy). Results: The serum level of Cys C (mg/L) was significantly higher in NHL patients compared to control subjects :1.03 (0.88–1.24)           vs 0.83 (0.78–0.90), P
Keywords: Cystatin C, Paraoxonase 1, non-Hodgkin lymphoma